Preoperative Anxiety Levels and Pain during Cataract Surgery. (2nd April 2020) - Socea, Sergiu D.; Abualhasan, Hamza; Magen, Or; Zayit-Soudry, Shiri; Blumenthal, Eytan Z.; Duvdevan, Nitsan; Mimouni, Michael
ABSTRACT: Purpose : To evaluate the correlation between pain during cataract surgery and preoperative anxiety. Methods : This prospective observational masked study included 103 eyes of 103 consecutive patients who underwent routine clear corneal incision phacoemulsification surgery at the Department of Ophthalmology, Rambam Health Care Campus, Haifa, Israel. Patients were interviewed prior to surgery and 5 min following surgery by two separate independent interviewers. Anxiety level was measured by the Visual Analog Scale for Anxiety (VASA) and pain by the Visual Analog Scale (VAS). The main outcome measure was the maximum amount of pain endured during the procedure using VAS. Results : The mean participant age was 68.9 ± 8.9 years, and 46.6% were male. Severe anxiety (VASA ≥ 7) and pain (VAS ≥ 7) were documented in 18.5 and 17.5% of patients, respectively. There was a statistically significant positive correlation between VAS and VASA (r = 0.62, p < .001) as well as between VAS and duration of surgery (r = 0.20, p = .04). There was no association between VAS and all other investigated parameters in the univariate analysis. In backward regression analysis, VASA was the only parameter that was significantly associated with VAS (R 2 = 36.61%, p < .001). Patients with severe anxiety were >10 times more likely to experience severe pain, and a VASA > 4 predicted severe pain with a sensitivity of 88.9% and a specificity of 69.4%. Conclusions : One-fifth of patients experienced severe anxiety and pain. Preoperative anxiety levels were the only significant predictor of pain. Reducing preoperative anxiety in cataract patients is warranted.